Implementation of "Pancasila Values" in the Context of Patriotism Using Storytelling Method in Class B Miftahul Ulum Al-Amin Terrak, Tlanakan, Pamekasan - Devi Sulistiani (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
Pancasila serves as a guideline for life for early childhood, especially in the context of patriotism and the values it upholds. In order to grow and develop, children need to be nurtured through habituation, independence, good manners, innovation, agility, hard work, and a sense of responsibility. Education based on Pancasila in daily activities can have a positive impact on early childhood, encouraging them to obey and internalize the values contained in Pancasila, which hold profound meaning for everyday life. This study uses a storytelling method and adopts a qualitative research type. Data collection is carried out in a specific area with a high level of accuracy in describing the phenomena that occur. The researcher will describe how the principles of Pancasila are implemented in the school activities of TK Miftahul Ulum Al-Amin Terrak, Tlanakan, Pamekasan, using the storytelling method. The research includes observation, documentation, and interview transcripts. Based on the observations conducted, in the implementation of a learning strategy based on the values of Pancasila in the context of patriotism using the storytelling method with the indicator of recognizing and understanding national symbols, the results show that 10 early childhood students understood these symbols, while 5 children had limited understanding of national symbols, the national anthem, and the meaning of Pancasila. Based on the research proposal entitled “The Implementation of Pancasila Values in the Context of Patriotism Using the Storytelling Method in TK B Class at Miftahul Ulum Al-Amin Terrak, Tlanakan, Pamekasan”, it can be concluded that character education based on Pancasila values is very important to instill from an early age. This indicates that education based on Pancasila values can create an inclusive and harmonious learning environment, enabling young children to easily understand and grasp these values.